TOURIST DESTINATION CHOICE MODELLING DURING COVID-19: CASE STUDY OF THE FIVE INDONESIA’S SUPER PRIORITY DESTINATIONS - Utari, Beatrice Amabella; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2021)
Tourism is one of the most important economic activities and was planned to be the core economy of Indonesia. During this COVID-19 pandemic, the period of self-isolation and other restrictions changed the tourists’ travel behavior and made tourism be the most affected industry. Government wanted to focus on the five of Indonesia's super-priority destinations; Borobudur, Labuan Bajo, Mandalika, Likupang, and Lake Toba, to recover the loss, but on the implementation, the ministry is not focused on the travel demand. This research aims to explore factors that affect Indonesian domestic tourists while choosing the five super-priority destinations during this COVID-19 and propose a recommendation to the tourism stakeholders. Using the choice modelling analysis, Mandalika government protocols, transportation cost, travel time; Labuan Bajo and Borobudur health and hygiene; and Borobudur destination image significantly influence tourist’s choice. The Health Enthusiast, Sports and Culture Person, and Nature-lover characteristics influence tourists in choosing destinations besides Lake Toba. The Social and Explorer characteristics influence them in choosing Lake Toba. Thus, the government should maintain periodic management controls of Cleanliness, Health, Safety, Environment Sustainability (CHSE) protocols and collaborate with tourism service providers to promote the five of Indonesia's super-priority destinations rooted in tourists' interest and safety guarantees.Keywords: Tourism, Choice Modelling, Destination Choice, Indonesia’s Super-Priority Destination